Regulation of Helicobacter pylori Urease and Acetone Carboxylase Genes by Nitric Oxide and the CrdRS Two-Component System - Madison G. McKinsey; Miranda Y. Bate; Lauren M. Tramonte; Emely Y. Avalos; John Loh; Timothy L. Cover; Mark H. Forsyth (Microbiology Spectrum)
ABSTRACT Helicobacter pylori colonizes the human gastric mucosa and causes various gastroduodenal diseases, including peptic ulceration and gastric cancer. Colonization requires the actions of two-component systems (TCSs) to sense and respond to changes in the host environment. In this study, we evaluated gene regulation mediated by the CrdRS TCS. Few studies have evaluated this TCS, leaving the signal(s) yet to be exhaustively determined and a need for a more complete regulon to be delineated. We performed RNA sequencing (RNA-Seq) on three isogenic H. pylori 26695 mutants: a control, a mutant with deletion of the sensory histidine kinase, ΔcrdS, and a mutant with deletion of the response regulator, ΔcrdR. Comparison of the RNA-Seq results from these mutants established a 40-gene regulon putatively controlled by the CrdRS TCS. Quantitative reverse transcriptase PCR (RT-qPCR) was used to validate 7 of 11 putative regulon members selected for analysis. We further investigated 6 confirmed CrdRS regulon genes by using phospho-incompetent H. pylori 26695 CrdR D53A and CrdS H173A mutants. These experiments further confirmed the role of CrdRS in regulation of urease, acetone carboxylase, hofD, and HP1440. Expression of these CrdRS regulon genes was also evaluated under 10 μM nitric oxide (NO) conditions. This revealed that ureA, acxA, hofD, and HP1440 expression is affected by NO in a CrdRS-dependent manner. Importantly, three of these genes (ureA, acxA, and hofD) are known to play important roles in H. pylori colonization of the stomach. IMPORTANCE The molecular strategies used by Helicobacter pylori to colonize and persist in the harsh environment of the human stomach are a critical area of study. Our study identified several genes in this gastric pathogen, including ureA, a gene encoding a protein essential to the survival of H. pylori, that are regulated via the CrdRS two-component system (TCS) in response to nitric oxide (NO). NO is a product of the innate immune system of the human host. The identification of these genes whose expression is regulated by this molecule may give insights to novel therapeutics. Two genes (ureA and acxA) determined in this study to be regulated by NO via CrdRS have been previously determined to be regulated by other TCSs, indicating that the expression of these genes may be of critical importance to H. pylori.